Pengaruh Modal dan Tenaga Kerja Terhadap Tingkat Pendapatan Pengusaha Tenun Di Desa Sukarara Kecamatan Jonggat Kabupaten Lombok Tengah - Fathurrahman, Fathurrahman; Aminy, Muhammad Habibullah (Jurnal Ilmiah Tata Sejuta STIA Mataram, 2021)
This research is entitled "Effect of Capital and Labor on Income Level of Weaving Entrepreneurs in Sukarara Village, Jonggat District, Central Lombok Regency". The purpose of the study was to analyze the effect of capital and labor on the income level of weaving entrepreneurs in Sukarara Village, Jonggat District, Central Lombok Regency. The research data was obtained from a questionnaire (primary) and several observations and direct interviews with stakeholders of the weaving industry. The results showed that the independent variables consisting of capital, labor had a significant effect on the income of weaving entrepreneurs at a significance level of 10 percent. Weaving capital affects the income of entrepreneurs, labor affects the income of entrepreneurs. As much as 99.2 percent of the variation of the independent variables as well as the variation of income variables used in this model, while the remaining 0.8 percent is explained by other variables.